Screening of Lentil (Lens culinaris Medik.) Genotypes and Correlation Analysis under PEG Imposed Water Stress Condition - Dash, Asit Prasad; De, Dilip Kumar; Mohanty, Soumitra; Lenka, Devraj (International Journal of Bio-resource and Stress Management, 2017)
The present experiment was carried out at the Department of Genetics and Plant Breeding, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India to screen lentil (Lens culinaris Medik.) genotypes for drought tolerance at seedling stage and to study the correlation among the seedling traits. For this purpose forty eight genotypes of lentil collected from AICRP on MULLaRP, Kalyani centre, Bidhan Chandra Krishi Viswavidyalaya, Nadia were evaluated for drought tolerance at seedling stage following slant glass plate method under pre-standardized -9.0 bar external water potential imposed by polyethylene glycol (MW-6000) against control (0.0 bar). The experiment was laid out in an asymmetrical factorial completely randomized design with three replications. Data from six randomly selected competitive seedlings on eleven growth parameters viz., root length (cm), shoot length (cm), total length (cm), root fresh weight (mg), shoot fresh weight (mg), leaf fresh weight (mg), total fresh weight (mg), root dry weight (mg), shoot dry weight (mg), leaf dry weight (mg) and total dry weight (mg) were recorded from ten days old seedlings from both control and treatment plate through destructive sampling. All the forty eight genotypes showed variable relative reduction % for all root and shoot traits under polyethylene glycol imposed water stress. Basing on drought tolerance efficiency, relative reduction % and the seedling growth parameters the genotypes were categorized as susceptible and tolerant to drought stress. Among the forty-eight genotypes, PL-406 (94.667%) exhibited the highest drought tolerance efficiency while L1112-20 (65.269%) exhibited the lowest drought tolerance efficiency. Correlation analysis revealed that, total dry weight attained a strong positive significant association with root dry weight followed by total fresh weight. All the traits except root length and total length attained significant positive correlation with total dry weight. Total fresh weight exhibited a higher direct effect on total dry weight which is the measure of drought tolerance at seedling stage.